2014
DOI: 10.1371/journal.pone.0093692
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Gene Polymorphisms and Environmental Factors on Oral Cancer Susceptibility in Taiwan

Abstract: BackgroundOral squamous cell carcinoma (OSCC) is the fourth leading cause of male cancer death in Taiwan. Exposure to environmental carcinogens is the primary risk factor for developing OSCC. CD44, a well-known tumor marker, plays a crucial role in tumor cell differentiation, invasion, and metastasis. This study investigated CD44 single-nucleotide polymorphisms (SNPs) with environmental risk factors to determine OSCC susceptibility and clinicopathological characteristics.Methodology/Principal FindingsReal-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 46 publications
0
35
0
1
Order By: Relevance
“…Winder et al [15] found CD44rs 187116 to be significantly associated with tumor recurrence in gastric adenocarcinoma, Zhou et al [20] found CD44 rs187116 to be involved in breast cancer progression. The CD44 rs187115 polymorphism has potential predictive significance in oral carcinogenesis in Taiwanian population [29].…”
Section: Discussionmentioning
confidence: 99%
“…Winder et al [15] found CD44rs 187116 to be significantly associated with tumor recurrence in gastric adenocarcinoma, Zhou et al [20] found CD44 rs187116 to be involved in breast cancer progression. The CD44 rs187115 polymorphism has potential predictive significance in oral carcinogenesis in Taiwanian population [29].…”
Section: Discussionmentioning
confidence: 99%
“…14 Moreover, both CD44 v3 and c-Met are upregulated in OSCC. [15][16][17][18] Our previous studies have shown that the overexpression of miR-143 is closely related to invasion and migration ability in the OSCC cell lines. To investigate whether c-Met was associated with the role of miR-143emediated inhibition of invasion and migration in OSCC cells, the expression level of phosphorylation c-Met was identified by using Western blot.…”
Section: Mir-143 Suppresses the Expression Of C-met By Targeting Cd44 V3mentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC), the most common primary malignancy occurring in the head and neck, has approximately 500, 000 new cases reported each year [1] and is the fourth most common male cancer and the fourth leading cause of male cancer death in Taiwan [2]. The use of tobacco and alcohol has been associated with oral cancer [3,4].…”
Section: Introductionmentioning
confidence: 99%